PENGEMBANGAN SKENARIO PEMBELAJARAN TEKS PERSUASI MENGGUNAKAN MODEL PROJECT BASED LEARNING DI SMP - Hayati, Jamilah; Ariyani, Farida; Liswati, Khoerotun Nisa (FKIP Universitas Lampung, 2020)
The problem of this research is learning scenario using persuasive text through project based learning model. Related to the problem above, the aims of this study was to develop a learning scenario by using persuasive text through project based learning model in junior high school and its feasibility as a persuasion text learning scenario.The researcher used ?R? and ?D? method, ?Research? and ?Development. The result of this research was product of learning scenario using persuasive text learning scenario product through project based learning model in junior high school. The assessment of seven indicators of the eligibility by material experts gained an average percentage of 92.8% with very good criteria. Further, the assessment of nine indicators by linguists acquired an average percentage of 77.8% by using good criteria. Masalah dalam penelitian ini adalah skenario pembelajaran teks persuasi menggunakan model project based learning. Tujuan penelitian ini ialah mengembangkan skenario pembelajaran teks persuasi menggunakan model project based learning di SMP dan kelayakannya sebagai skenario pembelajaran teks persuasi. Penelitian ini menggunakan metode R and D atau research and development. Hasil penelitian pengembangan yang dilakukan adalah produk skenario pembelajaran teks persuasi menggunakan model project based learning di SMP dengan enam tahapan pembelajaran. Hasil penilaian dari tujuh indikator oleh ahli materi memperoleh rerata persentase 92,8% dengan kriteria sangat layak. Hasil penilaian dari sembilan indikator oleh ahli bahasa memperoleh rerata persentase 77,8% dengan kriteria sangat layak digunakan. Keywords: scenario learning, project based learning, persuasive text